Diagnostic Utility of GeneXpert MTB/RIF Assay in EPTB Detection in Formalin Fixed Paraffin Embedded Tissue Biopsies in South Western Uganda - Kasadha R; Atwine R; Kassaza K; Nabaasa S; Amadile L; Tibenderana L; Ninsiima LJ; Wasswa H; Mwangi FG; Ssedyabane F (Dove Medical Press, 2024)
Richard Kasadha,1,2 Raymond Atwine,3 Kennedy Kassaza,4 Saphurah Nabaasa,1 Lawrence Amadile,1 Lauben Tibenderana,1 Lydia Jolly Ninsiima,1 Hassan Wasswa,1 Fridah Gakii Mwangi,1 Frank Ssedyabane1 1Department of Medical Laboratory Science, Mbarara University of Science and Technology, Mbarara, Uganda; 2UPDF Military Health Services, Ministry of Defence and Veteran Affairs, Bombo, Uganda; 3Department of Pathology, Mbarara University of Science and Technology, Mbarara, Uganda; 4Genomics and Translational Laboratory, Department of Microbiology, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Richard Kasadha, Email kasadhar3@gmail.comPurpose: Formalin-fixed tissue biopsies submitted to the Histopathology Laboratory were explored for possible use in the GeneXpert MTB/Rifampicin assay for EPTB diagnosis, therefore this study aimed to determine the diagnostic utility of the GeneXpert MTB/RIF assay in EPTB detection in formalin-fixed paraffin-embedded tissue biopsies using Ziehl-Neelsen (ZN) and Haematoxylin and Eosin (H&E) staining as a composite reference standard.Methods: A total of 89 selected archived formalin-fixed paraffin-embedded tissues with histological features of tuberculosis were included in the study. ZN and H&E staining were performed as a composite reference standard, followed by GeneXpert MTB/RIF assay as diagnostic test. Data were analysed using STATA software version 17.0.Results: Of the 89 specimens enrolled, 55% were male. The Lymph node was the commonest site (64%). 15/89 (16.9%) cases were positive for ZN, 45/89 (50.6%) were positive for H&E and 27/89 (30.3%) were positive for GeneXpert. The overall sensitivity and specificity of GeneXpert were 48.94% (95% CI: 38.55%- 59.32%) and 90.48% (95% CI: 84.38%- 96.57%), respectively, in lymph node tissues, were 52.94% (95% CI: 39.98%- 65.90%) and 82.61% (95% CI: 72.77%- 92.45%), respectively, and in Non-Lymph node tissues, were 38.46% (95% CI: 21.61%- 55.32%) and 100% (95% CI: 100%- 100%), respectively.Conclusion: The GeneXpert MTB/RIF assay is a potential tool for diagnosing EPTB in FFPE tissues and may be used in the development of an algorithm in the histopathology laboratory.Keywords: sensitivity, specificity, genexpert, ZN, H&E, EPTB